Effect of Residual Stone Fragments on Patient-Reported Quality of Life after Endoscopic Kidney Stone Surgery - Sang Hee Lee; Jun-Koo Kang; Jae-Wook Chung; Yun-Sok Ha; Jun Nyung Lee; Seock Hwan Choi; Hyun Tae Kim; Tae-Hwan Kim; Eun Sang Yoo; Tae Gyun Kwon; Bum Soo Kim (Urogenital Tract Infection)
Purpose This study examined the effects of residual fragments (RF) on the patient-reported quality of life (QOL) after kidney stone surgery, such as retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL), using the Korean version of the Wisconsin Stone Quality of Life Questionnaire (K-WISQOL). Materials and Methods The medical records of 156 patients who underwent RIRS or PCNL and completed the preoperative and postoperative K-WISQOL from January 2021 to September 2023 were analyzed retrospectively. The patients were divided into RIRS and PCNL groups by the surgical method. The participants completed the K-WISQOL within four weeks before and after treatment. The patients’ baseline characteristics, surgical outcomes, and K-WISQOL scores were compared according to the presence of RF in each surgical group. Results Of the 156 patients, 95 underwent RIRS, and 61 underwent PCNL. In the RIRS group, the patients’ baseline characteristics and surgical outcomes were similar in the stone-free (SF) and RF subgroups. The changes in all K-WISQOL domain scores and total scores were similar in the two subgroups. In the PCNL group, the RF subgroup had a significantly higher proportion of staghorn stones, a significantly larger mean stone diameter and significantly longer operation time than those of the SF subgroup. But, the changes in all K-WISQOL domain scores and total scores were not significantly different between the two subgroups, as observed in the RIRS group. Conclusions This study showed that the presence of RFs after endoscopic kidney surgery did not affect the short-term patient-reported QOL regardless of the surgical methods.